Ảnh hưởng của văn hoá doanh nghiệp đến phát triển bền vững tại các doanh nghiệp ngành hóa chất Việt Nam - Lê Phú , Khánh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Although the relationship between organizational culture and corporate sustainability has been widely examined, limited research has investigated which types of organizational culture drive environmental sustainability in emerging economies, particularly in Vietnam’s chemical industry. Grounded in the Competing Values Framework (CVF), this study examines the effects of hierarchy, adhocracy, clan, and market cultures on environmental sustainability while testing the mediating role of green process innovation capability. Data were collected from 323 chemical enterprises in Vietnam and analyzed using structural equation modeling. The results indicate that adhocracy culture has a significant positive effect on environmental sustainability. In addition, green process innovation serves as a mediator in the relationships between market culture, adhocracy culture, and environmental sustainability